Serum Leptin levels in ovarian polycystic disease and its correlation to body weight - Shalal, Maad M.; Miran, Najmah M.; Mahddi, Zina I. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Poly cystic ovary syndrome is a common disorder in women of reproductive age, it is associated with disturbance of reproductive, endocrine and metabolic functions. The pathophysiology of PCOS appears to be multifactorial and polygenic. Leptin seems to play an important role in pathophysiology of PCOS especially in women with BMI ≥25kg/m2. J Fac Med Baghdad 2014; Vol.56, No .2 Received Sept .2013 Accepted April. 2014 Objectives: To assess leptin level in both PCOS and healthy women and explore the relation to their body weight and body mass index. Patient and Methods: A total of 120 women were enrolled in this study, 60 women (50%) had PCOS (study group) and the reminder 60 women (50%) were healthy women and considered as control group. BMI was calculated first. Both groups were further subdivided into two groups; BMI of ≥25kg/m2 and BMI of <25kg/m2. Pelvic U/S scan was done to confirm the diagnosis. Hormonal profile (FSH, LH, LH/FSH, testosterone, TSH, T4 and prolactin) were measured. RBS was measured. Serum leptin level was measured in patient with PCOS and the control by Enzyme linked immunesorbant assay (ELISA) test. Correlations between leptin levels and age, Wt, Ht, BMI, and serum hormone levels (FSH, LH, testosterone and prolactin) were studied. Results: Mean serum leptin levels were not significantly higher in patients with PCOS compared to the control group (P =0.052). Leptin levels were found to be higher significantly in the overweight subgroups both in patients with PCOS and in the control women. Leptin levels were found to be higher in over weight patients with PCOS compared to over weight control P value =0.0001. Serum leptin levels were significantly correlated with BMI in both patient with PCOS and control group (r=0.918 and r=0.846) respectively. Serum leptin concentration had a positive correlation with serum LH concentration in PCOS group (r=0.327). Leptin levels had strong positive correlation with serum LH, FSH, and testosterone in over weight PCOS subgroup women and (r=0.592, 0.609 and 0.604) respectively. Conclusion: Leptin levels are higher in patient with PCOS compared to control groups. Leptin levels were correlated with the amount of fatty tissue not only in PCOS group but also in healthy women. Leptin play an important role in pathophysiology of PCOS of women with BMI ≥25 kg/m2.